Significant changes in dividend policy and insider trading activity on the Johannesburg Stock Exchange - Narendra Bhana (South African Journal of Business Management, 1991)
The objective with this article was to determine whether insider trading related to unannounced dividend policy changes provided abnormal returns for shares listed on the Johannesburg Stock Exchange (JSE). The results indicate that insiders as a group seem to exhibit 'remarkable timing ability'. Significant changes in insider trading activity were detected during the six-month period prior to the resumption (omission) announcement. Company insiders trading prior to dividend changes announcements earned consistently large positive abnormal returns (avoid large negative abnormal returns). It is recommended that company insiders be required to make public the market positions they take in their company's shares. This can be expected to reduce the abnormal returns derived from insider trading and will also contribute towards improving the efficiency of the JSE.
Keywords: 650